Novel KV7 ion channel openers for the treatment of epilepsy and implications for detrusor tissue contraction. Issue 23 (15th December 2018) - Seefeld, Mark A.; Lin, Hong; Holenz, Joerg; Downie, Dave; Donovan, Brian; Fu, Tingting; Pasikanti, Kishore; Zhen, Wei; Cato, Matthew; Chaudhary, Khuram W.; Brady, Pat; Bakshi, Tania; et al.
Graphical abstract: Highlights: Novel pan-Kv7 openers for the treatment of epilepsy are discussed. Compounds from two series of Kv7 openers show efficacy in PTZ and MES-T seizure models. Bladder contraction is associated with pan-Kv7 activity, but perhaps not with homomeric Kv7.4 activity as reported. Abstract: Neuronal voltage-gated potassium channels, KV 7s, are the molecular mediators of the M current and regulate membrane excitability in the central and peripheral neuronal systems. Herein, we report novel small molecule KV 7 openers that demonstrate anti-seizure activities in electroshock and pentylenetetrazol-induced seizure models without influencing Rotarod readouts in mice. The anti-seizure activity was determined to be proportional to the unbound concentration in the brain. KV 7 channels are also expressed in the bladder smooth muscle (detrusor) and activation of these channels may cause localized undesired effects. Therefore, the impact of individual KV 7 isoforms was investigated in human detrusor tissue using a panel of KV 7 openers with distinct activity profiles among KV 7 isoforms. KCNQ4 and KCNQ5 mRNA were highly expressed in detrusor tissue, yet a compound that has significantly reduced activity on homomeric KV 7.4 did not reduce detrusor contraction. This may suggest that the homomeric KV 7.4 channel plays a less significant role in bladder contraction and further investigation is needed.